Genocide and resistance Nr. 28(2) - Labanauskas, Ramūnas; Buchaveckas, Stanislovas; Pocius, Mindaugas; Vaičiūnas, Gintaras; Selenis, Valdas; Klumbys, Valdemaras; Stravinskienė , Vitalija; Bargmanas, Chaimas (Genocidas ir rezistencija, 2010)
Full Issue